EFFECT OF TEMPERATURE ON FRESHWATER - Pandurang D. Jankar; Sharad S. Adlinge (International Journal of Innovations in Engineering Research and Technology, 2022)
This study has proposed to determine the effects of water temperature in between 28 and 34 ºC on the growth of cultivable fish Common carp, Cyprinuscarpiofor freshwater aquaculture. Four similar (50 l capacity) dimension aquariums (T1; 28 ºC, T2; 30 ºC, T3; 32 ºC and T4; 34 ºC, respectively) were taken for this 21 days experiment. They were fitted with mechanical and bio-filter, high-performance air compressor aerator, automatic heater with thermostat and alcohol thermometer. Recirculation set up was arranged in all aquariums to maintain identical parameters except the temperature alone. Standard management procedures were adopted such as pre-stocking, stocking and post stocking management. Fishes were slowly acclimatized in their appropriate aquarium temperature before the initial morphometric measurements. Feed percentage was 5% of their total body mass of ten fishes in eachaquarium